Cartografía de precipitaciones y temperaturas en el valle medio del Ebro mediante la utilización de diferentes técnicas estadísticas - Vicente Serrano, Sergio; Saz Sánchez, Miguel Ángel (Geographicalia, 2016)
This work analyses the final quality of different continuous cartographies of precipitation and temperatures carried out using different interpolation techniques. The analysis has been performed in the central Ebro valley, an area with flat topography but complex climatic patterns. 23 maps of temperature and precipitation have been performed with different methods (local, global and geostatistics). The best results in the precipitation maps have been obtained by means of geostatistical rnethods. Block-kriging and cokriging provide the best results for the interpolation of precipitation. Regression model provide the higher quality results for temperature interpolation. The utility of different mapping methods is discussed.